2021
DOI: 10.1371/journal.pone.0258236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a hospital-wide campaign on COVID-19 vaccination uptake among healthcare workers in the context of raised concerns for life-threatening side effects

Abstract: Background All healthcare workers (HCWs) in Yongin Severance Hospital were allocated to receive the ChAdOx1 nCov-19 vaccine according to national policy. A report of thrombosis and thrombocytopenia syndrome (TTS) associated with ChAdOx1 nCoV-19 led to hesitancy about receiving the second dose among HCWs who had received the first dose. Methods From 7 to 14 May, 2021, we performed a survey to identify the factors associated with hesitancy about receiving the second vaccine dose among HCWs at the hospital who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…A structured self-administered questionnaire, adapted from Kim et al study in China [ 24 ]. The questionnaire was reviewed and pilot tested on 30 HCWs to check the acceptability and clarity of the questions.…”
Section: Methodsmentioning
confidence: 99%
“…A structured self-administered questionnaire, adapted from Kim et al study in China [ 24 ]. The questionnaire was reviewed and pilot tested on 30 HCWs to check the acceptability and clarity of the questions.…”
Section: Methodsmentioning
confidence: 99%
“…Previous vaccination habits, particularly regarding influenza, were correlated with support for/receiving COVID-19 vaccination [54,56,76,114,115]. This suggests that hesitancy for the COVID-19 vaccine may be rooted in previous vaccine hesitancy.…”
Section: Demographics Of Vaccine Hesitant Hcwsmentioning
confidence: 96%
“…Sending out reminders or email "nudges" as one institution did, might also be useful [250]. Organizations have also reported success in increasing vaccination rates using "drives" or institution-wide vaccination campaigns [115].…”
Section: Towards the Futurementioning
confidence: 99%
“…A systematic review of global COVID-19 vaccine intentions during the COVID-19 pandemic revealed varying levels of self-reported intentions among nurses (40–63%), healthcare workers (28–77%), and doctors and trainees (62–78%) (Sallam, 2021 ). Although intentions were poorer, studies conducted later during the pandemic revealed high COVID-19 vaccine uptake (Green-Mckenzie et al, 2021 ; Kim et al, 2021 ), suggesting health campaigns, organizational policies, and vaccine mandates were effective at increasing coverage (Schumacher et al, 2021 ). Despite this intended positive outcome, some HCPs report concerns about COVID-19 vaccines (Kim et al, 2021 ), and many studies point to low influenza vaccine coverage among providers (Dubé et al, 2014 ; Genovese et al, 2019 ; Lam et al, 2010 ; To et al, 2016 ) indicating vaccine campaigns and interventions can be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…Although intentions were poorer, studies conducted later during the pandemic revealed high COVID-19 vaccine uptake (Green-Mckenzie et al, 2021 ; Kim et al, 2021 ), suggesting health campaigns, organizational policies, and vaccine mandates were effective at increasing coverage (Schumacher et al, 2021 ). Despite this intended positive outcome, some HCPs report concerns about COVID-19 vaccines (Kim et al, 2021 ), and many studies point to low influenza vaccine coverage among providers (Dubé et al, 2014 ; Genovese et al, 2019 ; Lam et al, 2010 ; To et al, 2016 ) indicating vaccine campaigns and interventions can be further improved. This hesitancy indicates potential gaps in the application of behavioural interventions and current vaccine-related communication.…”
Section: Introductionmentioning
confidence: 99%